Medical device regulations : global overview and guiding principles. - Cheng, Michael (World Health Organization, 2003)
Medical devices and equipment are a vital component of patient care. From a simple tongue depressor to a sophisticated haemodialysis machine, medical devices are needed at every level of the health service. Yet many health services continue to lack information and financial resources to acquire the devices they really need, i.e. those that will address the specific disease burden in their country. Effective implementation of a National Regulatory Authority is a first step towards the cost-effective management of medical devices that meet international quality and safety standards, throughout t.